Valproic acid exposure decreases neurogenic potential of outer radial glia in human brain organoids - Zang, Zhenle; Yin, Huachun; Du, Zhulin; Xie, Ruxin; Yang, Ling; Cai, Yun; Wang, Liuyongwei; Zhang, Dandan; Li, Xin; Liu, Tianyao; Gong, Hong; Gao, Junwei; et al. (Frontiers in Molecular Neuroscience, 2022)
Valproic acid (VPA) exposure during pregnancy leads to a higher risk of autism spectrum disorder (ASD) susceptibility in offspring. Human dorsal forebrain organoids were generated from human embryonic stem cells (hESCs) and utilized for recapitulating the three-dimensional architecture and consequence on the developing human brain after using VPA during pregnancy. We found that VPA exposure in organoids caused a reduction in the size and impairment in the proliferation and expansion of neural progenitor cells (NPCs) in a dose-dependent manner. VPA exposure typically decreased the production of outer radial glia-like cells(oRGs), a subtype of NPCs contributing to mammalian neocortical expansion and delayed their fate toward upper-layer neurons. Transcriptomics analysis revealed that VPA exposure influenced ASD risk gene expression in organoids, which markedly overlapped with irregulated genes in brains or organoids originating from ASD patients. We also identified that VPA-mediated Wnt/β-catenin signaling pathway activation is essential for sustaining cortical neurogenesis and oRGs output. Taken together, our study establishes the use of dorsal forebrain organoids as an effective platform for modeling VPA-induced teratogenic pathways involved in the cortical neurogenesis and oRGs output, which might contribute to ASD pathogenesis in the developing brain.